2019
DOI: 10.1186/s12885-019-6251-7
|View full text |Cite
|
Sign up to set email alerts
|

SMAD4 Y353C promotes the progression of PDAC

Abstract: BackgroundSMAD4 is frequently inactivated and associated with a poor prognosis in pancreatic ductal adenocarcinoma (PDAC). Abnormal SMAD4 expression also plays an important role in the malignant progression of PDAC.MethodsWe investigated SMAD4 status in PDAC by immunohistochemical methods to explore the relationships between SMAD4 expression and clinicopathological features and then detected SMAD4 mutations by Sanger sequencing in 95 patients with PDAC to identify new mutation sites in PDAC. We further evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 52 publications
1
21
0
Order By: Relevance
“…We tested this in vitro and found that miR-483-3p promoted cell migration and invasion in transwell assays. These findings are consistent with known functions of the putative miR-483-3p target SMAD4 53,54 and further suggest that miR-483-3p may play a key role in PDAC progression.…”
Section: Dovepresssupporting
confidence: 89%
“…We tested this in vitro and found that miR-483-3p promoted cell migration and invasion in transwell assays. These findings are consistent with known functions of the putative miR-483-3p target SMAD4 53,54 and further suggest that miR-483-3p may play a key role in PDAC progression.…”
Section: Dovepresssupporting
confidence: 89%
“…Besides, TMB has emerged as a promising novel biomarker in predicting the prognosis and immune response in various cancers ( 29 ). We discovered that high mutation rates were associated with genes ( KARS and TP53 ) ( 30 ), which were mostly related to cancer progress, tumor angiogenesis, and metastasis ( 31 33 ). TICS showed a modest negative relationship with the TMB score ( r = −0.28, p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…181 Mutations in the genes that encode Smad transcription factor proteins, which are key mediators of TGF-β signalling, can promote TGF-β-mediated EMT. 182,183 Furthermore, driver mutations in the APC, CTNNB1 and NOTCH1 genes, and other components of the WNT and Notch signalling pathways, contribute to EMT in various cancers. [184][185][186] Miscellaneous genes As a consequence of mutation, genes that are not directly related to the regulation of cell movement can sometimes acquire new functions and thus promote cancer cell migration and invasion.…”
Section: Emt Regulatorsmentioning
confidence: 99%